ETIKA MENGINGAT BAGI BANGSA PELUPA - Binsar J. Pakpahan (Jurnal Ledalero, 2017)
Indonesians have the tendency to forget their problems as a way of solving them. The main question to be explored in this paper is who has the task to remember, and what to remember. Forgetfulness is thought to come from several factors: language, the manner one accepts things that happened, and as an escape from problems that are considered unsolveable. Memory has become a political commodity when it is remembered or forgotten for certain goals. Nevertheless, to remember is better than to forget in terms of dealing with the painful past. Remembering is our responsibility to hear the voice of the victims of history, so that tragic history will not repeat itself. Some Indonesian ethnic groups have shown that they have a basis for remembrance in their culture and we can use this as a basis for communal remembrance in dealing with the painful past. Keywords: remember, forget, Indonesian language, communal memory,truth, history, responsibility Bangsa Indonesia memiliki kebiasaan untuk melupakan masalah yang ada. Pertanyaan utama yang akan dieksplorasi adalah, siapa yang memiliki tugas utama untuk mengingat, dan apa yang harus diingat. Kebiasaan untuk melupakan di Indonesia muncul dari beberapa faktor: bahasa, penerimaan akan kejadian yang dialami, dan pelarian dari masalah yang dianggap tidak bisa diselesaikan. Ingatan juga menjadi sebuah komoditas politik ketika dia diingat dan dilupakan demi tujuan tertentu. Meskipun menyakitkan, mengingat masa lalu untuk perubahan di masa depan adalah pilihan yang lebih baik dari melupakannya. Mengingat adalah tanggung jawab kepada para korban dalam sejarah supaya suara mereka terdengar, masa lalu tidak terulang lagi, dan perjalanan sebuah bangsa ke depan. Beberapa suku di Indonesia menunjukkan bahwa tindakan mengingat juga ada dalam budaya dan dia dapat digunakan menjadi dasar ingatan komunal bagi bangsa Indonesia dalam penyelesaian kasus-kasus masa lalu yang menyakitkan. Kata-kata kunci: mengingat, melupakan, bahasa Indonesia, ingatan komunal, kebenaran, sejarah, tanggung jawab